2020
DOI: 10.1371/journal.pone.0230915
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of secondary alcohol dehydrogenase in Nocardia cholesterolicum NRRL 5767 by CRISPR/Cas9 genome editing technology

Abstract: Nocardia cholesterolicum NRRL 5767 is well-known for its ability to convert oleic acid to 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 74 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…This allows the UV-vis spectrophotometric monitoring of NADH production over time as a measure of Ohy activity under the right conditions. The 10-HSA oxidation activity was already reported in microbial whole cell reactions (Niehaus et al 1978), and a number of 10-HSA converting alcohol dehydrogenases have been identified (Huang et al 2020;Wu et al 2019). ADH010 and ADH020 out of a commercial screen of ten different NAD +dependent alcohol dehydrogenases (Evoxx, Monheim am Rhein, Germany) were found to convert 10-HSA efficiently (Busch et al 2020b).…”
Section: Enzyme Activity Assaysmentioning
confidence: 91%
“…This allows the UV-vis spectrophotometric monitoring of NADH production over time as a measure of Ohy activity under the right conditions. The 10-HSA oxidation activity was already reported in microbial whole cell reactions (Niehaus et al 1978), and a number of 10-HSA converting alcohol dehydrogenases have been identified (Huang et al 2020;Wu et al 2019). ADH010 and ADH020 out of a commercial screen of ten different NAD +dependent alcohol dehydrogenases (Evoxx, Monheim am Rhein, Germany) were found to convert 10-HSA efficiently (Busch et al 2020b).…”
Section: Enzyme Activity Assaysmentioning
confidence: 91%
“…There is a report of application of genome editing technology employing CRISPR/Cas9 technique to desirably knockout secondary alcohol dehydrogenase in N. cholesterolicum [73], if such technology is employed in case of rubber degrading microbes, we can expect positive outputs. To cope up with the threat of Nocardia contaminated wastes, lytic bacteriophages can be used, as a similar case has been reported for biocontrol of Nocardia-stabilized foams in activated sludge plants by lytic bacteriophage GTE2 [74].…”
Section: Presence Of Virulence Factors In the Genome Sequencesmentioning
confidence: 99%
“…All of the 157 possible gRNAs sequences that can target PAM (Protospacer Adjacent Motif) sequences were analyzed based on efficiency and off-targets for mismatches. Four possible 24 nucleotides long protospacer sequences (4 nt 5' sticky end + 20 nt spacer sequence) with the sticky ends ACGC on the forward sequence and AAAC on the reverse sequence were chemically synthesized [19]. The protospacer sequence was generated by equimolar ligation as previously reported (Supplementary Figure S1) [19].…”
Section: Design and Construction Of Sgrnas Plasmidsmentioning
confidence: 99%
“…Four possible 24 nucleotides long protospacer sequences (4 nt 5' sticky end + 20 nt spacer sequence) with the sticky ends ACGC on the forward sequence and AAAC on the reverse sequence were chemically synthesized [19]. The protospacer sequence was generated by equimolar ligation as previously reported (Supplementary Figure S1) [19]. The gRNA sequence containing sticky end overhands was inserted into CRISPomyces-2 plasmid using golden-gate assembly protocol using Bbs1 (type IIs restriction enzyme) (Supplementary Figure S1) [20].…”
Section: Design and Construction Of Sgrnas Plasmidsmentioning
confidence: 99%